Keberhasilan Implementasi Kebijakan Dana BOS terhadap Kualitas Pendidikan di SMP PGRI 1 CIAMBAR - Amir Mirdad; Istikhori Istikhori; Tedi Tedi; Emat Muslihat; Toha Suryana (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
The purpose of this research and community service is to identify the problems that occur in the Sukamulya Cikupa Tangerang community and to conduct outreach activities on the role of parents in shaping a generation with Islamic character in the digital era. The method used is Participatory Action Research (PAR). The PAR method is a research and community empowerment approach that positions the community as active participants in the process of identifying problems and designing solutions. This outreach activity is the result of collaboration between residents, the Izzatin Nisa Islamic study group, Muhammadiyah University of Tangerang, and local community leaders. The community service was carried out at Maditerania Residence Sukamulya, Cikupa District, Tangerang Regency. The outreach participants consisted of housewives, teachers, community leaders, and factory workers, totaling 300 participants. The resource person in this outreach activity was a lecturer from Muhammadiyah University of Tangerang. The results of this research and community service are that there are negative impacts of digital technology devices on the younger generation. To prevent these negative impacts, the role of parents is needed in educating, supervising, and providing digital literacy provisions to the younger generation to avoid negative impacts. There is also a need for public education regarding the role of parents in shaping a young generation with Islamic character in accordance with Islamic teachings in the digital era.